Analisis Penetapan Harga Jual Produk CV. Abah Ayi Dengan Metode Cost Plus Pricing - Raka Fahrizal Irwansyah; Santi Pertiwi Hari Sandi; Syifa Pramudita Faddila (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The selling price should identify all costs that make a profit in the long run. Cost plus pricing, namely setting the cost by including a factor (percentage) of the selling price or cost in profit. The purpose of this study is to understand how companies determine the selling price of their products using the cost plus CV method. Abah Ayi. Analyze this data using quantitative methods. Research results show that CV. Abah Ayi determines the selling price of their products using traditional methods. The cost calculation of the manufacturing process done by the business owner is not detailed enough, and some costs are calculated using estimated costs. The selling price of products according to this method is lower than the selling price of CV products. Abah Ayi, to earn more profit. The initial production cost of Rp 27,500 becomes Rp 23,000 with the selling price of Rp 30,000 for duck rice, while the initial production cost of Rp 25,000 becomes Rp 21,000 with the same selling price of Rp 27,500 for chicken rice. Research data shows that the difference in profits generated is quite large and the use of cost and markup methods is more effective. Keywords: Selling Price, Cost Plus Pricing, CV. Abah Ayi.